Edukasi Label Informasi Gizi sebagai Upaya Meningkatkan Pengetahuan Remaja tentang Jajanan Sehat pada Siswa SMAN 35 Jakarta - Maya Fernandya Siahaan; Dessy Aryanti Utami; Isniati Dwijayanti; Muthia Farah Diba Damanik (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
One of the nutritional problems that often occur in school children is the habit of consuming snacks. Snacks sold in the school environment often do not meet food safety and nutrition standards. Students of SMAN 35 Jakarta spend a lot of time at school and mostly consume food available in the school canteen. While the school canteen is dominated by traders who provide packaged food and beverages. Their decision in choosing the food and beverages consumed will certainly affect their health status. This study aims to increase knowledge about food label information, through this activity it is also expected that students will become wiser in choosing packaged foods to suit their body's needs to achieve optimal nutrition. Educational materials are delivered through interactive lectures with the support of visual aids in the form of e-booklets. Based on the results of community service activities in the form of nutrition education at SMAN 35 Jakarta, there is an increase in the knowledge and ability of students about the importance of knowing the nutrition information label on packaged products. Through this activity, it is also expected that students will become wiser in choosing packaged foods to suit their body's needs to achieve optimal nutrition.